Allicin mitigates fumonisin B1-induced kidney toxicity in quails: Modulating fibrosis, NF-κB signaling pathway, and mitochondrial damage - Yangwan Zhang; Yihao He; Xueyan Zhu; Yang Liu; Changyu Cao (Poultry Science, 2025)
Fumonisin B1 (FB1) is a common mycotoxin, which is a water-soluble metabolite produced through the metabolism of Fusarium verticillioides and Fusarium proliferator. Crops and feedstuffs are widely contaminated by FB1 from the environment, posing risks to livestock and human health. Currently, there is no therapeutic approach available for FB1 intoxication. Allicin, an organic sulfur compound extracted from garlic, exhibits anti-inflammatory, antioxidant, antibacterial, hepatoprotective, cardioprotective, and intestinal regulatory properties. However, investigations into allicin’s role in alleviating FB1-induced quail nephrotoxicity remain relatively limited. This study thus aimed to elucidate the mechanisms by which allicin exerts a protective effect against FB1-induced kidney injury in juvenile quails. A total of 150 juvenile quails were randomly divided into five groups and treated with varying allicin concentrations (0, 50, 100, 500, and 1000 mg/kg) for 8 weeks. The blood and kidney tissues were subsequently screened using serum biochemical indices and histological staining, which suggested that 500 mg/kg of allicin was the optimal concentration that exerts protection to the quail kidneys. Another 120 juvenile quail were randomly divided into four groups (n = 30): control, allicin, FB1, and allicin+FB1. The pathological changes in kidney tissues induced by FB1 and genes associated with nuclear xenobiotic receptors (NXRs), inflammation, fibrosis, and mitochondrial damage were evaluated after 8 weeks. FB1 triggered kidney fibrosis and mitochondrial injury by activating the NF-κB signaling pathway, modulating NXR expression, and regulating corresponding CYP450 subtypes, which culminated in pathological injury to kidney tissues. Notably, allicin alleviated FB1-induced kidney injury in quails, possibly by inhibiting the NF-κB pathway, fibrosis, and mitochondrial damage, suggesting the potential application of allicin in preventing FB1-induced toxicity in quail.